La Temmassonge: Tokoh Kunci Pengembangan Islam di Kerajaan Bone Abad ke-18 - Amal, Arsy; M. Dahlan, (Rihlah: Jurnal Sejarah dan Kebudayaan, 2024)
During the reign of La Temmasonge Sultan Abdul Razak Jalaluddin, the 22nd King of Bone, he was known as a leader with a strong social conscience and a deep concern for the development of Islam in the Bone Kingdom. This study aims to analyze the role of La Temmasonge in the development of Islam in the Bone Kingdom in the 18th century. The research methods used include heuristics, source criticism, interpretation, and historiography. The findings indicate that, as a socially-minded leader, La Temmasonge actively strengthened Islamic values through the development of markets, rice fields, fish ponds, and mosques. The development of markets, rice fields, and fish ponds advanced the local economy, created business opportunities, and strengthened social interactions. Meanwhile, the construction of mosques supported access to religious education and reinforced Islamic identity in the community. La Temmasonge’s strategies had impacts not only on religious aspects but also brought significant changes to the social, economic, and political order in the Sulawesi Peninsula.